486 Assessment of blood metabolites in fed Holstein steers with and without liver abscesses. (7th December 2018) - Herrick, R; Jones, T; Sperber, J; Richeson, J; Brown, T; Lawrence, T
Abstract: Cattle with liver abscesses do not display any known clinical signs, and abscesses are only detected upon slaughter. Therefore, procedures to detect liver abscesses prior to slaughter are often time intensive and have yielded inconsistent results. The objective of this research was to compare whole blood and serum analyses from cattle with and without liver abscesses to quantify differences associated with the presence and severity of liver abscesses in fed Holsteins. Blood samples for complete blood count (CBC) and sera were collected from fed Holsteins (n = 153) approximately 30 s after exsanguination; liver abscesses were visually assessed after evisceration. Data were analyzed using mixed model ANOVA and logistic regression procedures of SAS v9.4 (SAS Inst. Inc., Cary, NC) with carcass serving as the experimental unit. Of the CBC variables analyzed, platelet counts were increased ( P = 0.02) and hemoglobin and hematocrit values ( P < 0.01) were decreased in carcasses with major abscesses (214 K/uL, 12.9 g/dL, 41.0%, respectively) when compared to carcasses without abscesses (137 K/uL, 13.8 g/dL, 43.4%, respectively). Serum analysis indicated that carcasses with major abscesses had increased ( P < 0.01) globulin (5.8 g/dL) and total protein (8.6 g/dL) concomitant with decreased ( P ≤ 0.03), albumin (2.8 g/dL), alanine aminotransferase (19 u/L) and aspartate aminotransferase (89 u/L) when compared to carcasses with no liver abscess (5.2 g/dL; 8.2 g/dL; 3.0 g/dL; 21 u/L; 97 u/L, respectively). Logistic regression using CBC variables (platelets and hemoglobin) or serum variables (aspartate aminotransferase and total protein), yielded equations that were able to explain 72% (c-statistic = 0.72) and 69% (c-statistic = 0.69) of the area under the curve, respectively, for estimating the probability of a major liver abscess. These results indicate that cattle with major liver abscesses undergo hematologic and metabolic differentiation which may be detected in whole blood and serum.